CURAHAN WAKTU KERJA WANITA TANI SEBAGAI BURUH PETIK MELATI GAMBIR DAN KONTRIBUSINYA TERHADAP PENDAPATAN RUMAH TANGGA - Muhammad Fauzan; Ulil Martinah; Lestari Rahayu (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2020)
This study aims to analyze the time spent of melati gambir pickers and their contribution to household income in Bukateja District, Purbalingga Regency. This study uses primary data from 52 respondents using a questionnaire and analyzed descriptively. The results showed that the time spend by melati gambir pickers was 37 hours / week. The income of melati gambir pickers was Rp. 596,346 / month and contributes 25.58% to total household income.